2022
DOI: 10.1016/j.psj.2021.101505
|View full text |Cite
|
Sign up to set email alerts
|

The composition of the lipid, protein and mineral fractions of quail breast meat obtained from wild and farmed specimens of Common quail (Coturnix coturnix) and farmed Japanese quail (Coturnix japonica domestica)

Abstract: The present study was intended to answer 2 scientific hypotheses: 1) the quail species has a significant influence in quail breast meat composition; 2) the wild quail's meat presents healthier composition than their farmed counterparts. An analysis of the pectoral muscles of wild and captive common quails ( Coturnix coturnix ) and domestic quails ( Coturnix japonica domestica ) was performed. The content of fatty acids (FA), amino acids, total cholestero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 37 publications
(50 reference statements)
0
10
0
1
Order By: Relevance
“…Table 2 shows the energy, mineral and vitamin requirements of quail production while the protein and amino acid requirements are presented in Table 3. Protein quality is generally based on the availability and composition of amino acids from the feedstuff following digestion (Quaresma et al, 2022). Out of a total of 19 amino acids, only 13 are required by quails, and these are considered as essential because they must be supplied in the diet and cannot be synthesized in the quail's body.…”
Section: Quail Nutrient Requirementmentioning
confidence: 99%
“…Table 2 shows the energy, mineral and vitamin requirements of quail production while the protein and amino acid requirements are presented in Table 3. Protein quality is generally based on the availability and composition of amino acids from the feedstuff following digestion (Quaresma et al, 2022). Out of a total of 19 amino acids, only 13 are required by quails, and these are considered as essential because they must be supplied in the diet and cannot be synthesized in the quail's body.…”
Section: Quail Nutrient Requirementmentioning
confidence: 99%
“…Quail meat contains a small amount of fat (3–4%) and a significant proportion of proteins (20%). In terms of vitamin and mineral content, quail meat is superior to the meat of broiler chickens [ 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, apart from egg production, carcass production traits and meat quality have become serious issues during the rearing processes. Studies have indicated that 8-week-old Japanese quail meat contains high protein and fat levels (23.32–24.55 g/100 g and 1.1–1.30 g/100 g, respectively) [ 1 ], but high cholesterol levels (71.07–87.0 mg/100 g) [ 1 , 2 ]. However, quail farming in Indonesia faces highly fluctuating temperature and humidity conditions; too high or low temperatures affect bird health, growth, product quality [ 3 ]; carcass quality [ 4 , 5 ]; body weight, carcass weight, carcass percentages [ 6 , 7 ]; immunity, nutrient digestibility, and product quality [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%